Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt. Istana Garmindo Jaya - Lia Apriyani; Sigit Purwanto; Widhi Ariyo Bimo (CV. ITTC INDONESIA, 2024)
This research aims to determine the effect of work motivation and work discipline on employee performance at PT. Garmindo Jaya Palace with a sample size of 70 respondents. The method used is a quantitative approach by distributing questionnaire research instruments to employees, and then processing them using a computer application, namely SPPS. This research was carried out at PT. Garmindo Jaya Palace with work motivation (X1) and work discipline (X2) variables on employee performance (Y) processed using correlation analysis, regression analysis, t-test, F test, and coefficient of determination. The results of this research use the t-test (partial) which shows the results that the work motivation variable has a partial effect on employee performance and the work discipline variable has a partial effect on employee performance. Meanwhile, the F test (simultaneous) shows that work motivation and work discipline on employee performance simultaneously or together influence employee performance at PT. Garmindo Jaya Palace.